Netosis as a bridge between inflammation and liver cell injury - Rycyk, Anna; Kasztelan-Szczerbinska, Beata; Cichoz-Lach, Halina (Journal of Education, Health and Sport, 2019)
One of programmed cell death types, netosis, discovered in ’96, was first described by Zychlinsky et al. and has gained elevating popularity among many researchers. It is a process occurring in order to catch pathogens into a trap and kill them. This trap is a scaffold somewhat consisting of chromatin and particles with antimicrobial properties such as histones. Extracellular histones are capable of proinflammatory cytokines production and platelets aggregation what accounts for inflammatory response. Unfortunately, these proteins have also a toxic potential which leads to cell injury through Toll like receptors presented by neutrophils. Mentioned neutrophils participate in an oxidative burst which yields to production reactive oxygen species performing a crucial role in the development of hepatocytes injury. Thus, alcohol abuse appears to result in a rapid development of liver cell injury through progression of inflammation induced by netosis. However, controlled NETs forming can be a future therapeutic option.